Coastal green infrastructure: reinforcement of coastal defences system as sustainable coastal practice at Pantai Kemasik, Kemaman, Terengganu/ Mohd Zahier Mazlan - Mazlan, Mohd Zahier (2017)
East coast area of Peninsular Malaysia is very famous with the existence of natural coastline that being the main contributor's towards tourism attraction. Tourists and local peoples love to visit coastal area as a recreational hub due to the attractive natural environment that far from city hustles and bustles. As a matter of fact, the coastal area is absolutely essential for various purposes such as for residential, recreational, tourism, marine activities and educational that contributes towards the development of socioeconomic for the local community. However, physical development has risen in these recent years. Coastline may change due to several factors; it can be either caused by natural or human activities. The most influenced factor is the erosion along the coastline. This factor is the main focus of this research paper. Many coastal areas in peninsular Malaysia suffer from erosion. One of the worst affected areas is the Pantai Kemasik, located in the district of Kemaman in east Malaysia. Over the last decades, Pantai Kemasik hit by erosion that cause by many factors and this phenomenon changed the original state of the coastline. In a time when coastal populations are growing and the number of coastal disasters is escalating, communities are beginning to look for a way to improve coastal defence system to create a resilient coastline for community. This study evaluates the potential of Coastal Green Infrastructure (CGI) strategies to protect shorelines from coastal erosion by the implementation of coastal defence system using the natural resources compared to manmade element. This approach normally practices the creation, restoration and emulating natural coastal features that varies in types. They are also beneficial in other aspect such as rebuild the habitat for wildlife upland and inland, improving water quality and also enhance the visual quality of a coastal area that can be a new attraction to the visitors.